Dampak pencemaran benzena terhadap lingkungan serta mekanismenya dalam memicu kanker: sebuah tinjauan literatur - Aldi, Davit (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2024)
Benzene (C6H6) is an aromatic hydrocarbon compound that is widely used in everyday life. However, the use of benzene compounds can endanger the environment and health because benzene is carcinogenic. This research was conducted to examine the negative effects of benzene as a trigger for disease and cancer. This research uses a descriptive qualitative analysis method to describe the process and negative impacts of benzene on humans and the environment. Benzene can settle in water or plants which are a source of animal feed and enter the food chain cycle, then reaches humans. Exposure to benzene, either directly or indirectly, can cause cancer in humans and animals. The direct impact of consuming food or drinks containing high levels of benzene can cause vomiting, stomach irritation, dizziness, drowsiness, seizures, rapid heart rate, coma, and death. Apart from the level of exposure, metabolic processes determined by genetics are factors that influence the impact. Humans with a high metabolic rate have a direct correlation with benzene levels in the body. The results of the paper conclude that benzene has a bad influence on living creatures which disrupts the final results of living creatures' metabolism.